Zimbabwe industrial equity index determinants in the multiple currency regime - Chikoko, Laurine; Samu, A. (Midlands State University, 2015)
The objective of this paper is to determine the sensitivity of the Zimbabwean Industrial equity index to fluctuations in macroeconomic variables. The research used an explanatory research design, through quantitative analysis employed on historical monthly time series from March 2009 to December 2011. Empirical results point to the existence of a long-run relationship between Zimbabwe Stock Exchange (ZSE) performance and interest rates, oil prices and the manufacturing index. Interest rates and international oil prices had a positive significant impact on the ZSE performance. However, the manufacturing index showed a significant negative relationship with the ZSE industrial index. The findings point to the fact that ZSE investors and potential investors should pay more attention to the trends of the aforementioned variables for them to consistently beat the market in the multiple currency era. Qualitative factors that are not incorporated in the study should be considered in making investment decisions, since the aforementioned variables are reported to account for only 67.09 percent of the variations in ZSE performance. Overally, the model exhibited that macroeconomic variables have a significant long run relationship with the ZSE performance; hence they are the leading indicators of the stock market performance.